2015
DOI: 10.4070/kcj.2015.45.5.416
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cardiovascular Risk Factors in Adults with Congenital Heart Disease

Abstract: Background and ObjectivesThe objective of this study was to analyze cardiovascular risk factors in adults with congenital heart disease (ACHD).Subjects and MethodsThe subjects for this study comprised 135 patients, aged 18 years and above, who visited the ACHD clinic at the Samsung Medical Center and 135 adults with a structurally normal heart who were randomly selected from the Center for Health Promotion during the same period. For the analysis, the ACHD group was further divided into an ACHD group that unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
3
14
1
1
Order By: Relevance
“…The proportion of overweight and obese patients in our study is consistent with published data on BMI in ACHD in Sweden . In contrast, our study showed a lower prevalence of smoking compared with several other studies on smoking behavior in patients with congenital heart disease . In our study, there was a slightly lower prevalence of diabetes mellitus than that previously reported …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The proportion of overweight and obese patients in our study is consistent with published data on BMI in ACHD in Sweden . In contrast, our study showed a lower prevalence of smoking compared with several other studies on smoking behavior in patients with congenital heart disease . In our study, there was a slightly lower prevalence of diabetes mellitus than that previously reported …”
Section: Discussionsupporting
confidence: 91%
“…24 In contrast, our study showed a lower prevalence of smoking compared with several other studies on smoking behavior in patients with congenital heart disease. [36][37][38] In our study, there was a slightly lower prevalence of diabetes mellitus than that previously reported. 16 Several studies have reported a high burden of cardiovascular There is a growing body of evidence that patients with congenital heart disease have a higher prevalence of ischemic heart disease compared with controls.…”
Section: Discussioncontrasting
confidence: 70%
“…Hyperlipidemia has been noted in surgically corrected ACHD patients but lower cholesterol is often seen in palliated or unrepaired CHD patients who remain cyanotic. 19,20 Almost 10% of patients in this series met criteria for metabolic syndrome 12,13 , and others have reported their prevalence of metabolic syndrome to be 1.5 times higher in ACHD patients than in health controls. 21 Based upon these findings, it appears prudent to consider at least guideline-based screening and management of ASCVD risk factors in the CHD population.…”
Section: Discussionmentioning
confidence: 64%
“…A Korean study showed a similarly higher rate of metabolic syndrome in the surgically corrected ACHD group of 37% versus 24% in control subjects. 290 Cyanotic CHD was protective against metabolic syndrome in this cohort.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 98%
“…308 A Korean study found low-density lipoprotein to be higher and high-density lipoprotein lower in patients with CHD than in a control group. 290 Low high-density lipoprotein and high triglycerides may be related to the same factors promoting metabolic syndrome in these patients. 289 Although data remain limited to single centers or administrative databases, the prevalence of dyslipidemia appears to be similar to that in the general population.…”
Section: Lipid Abnormalitiesmentioning
confidence: 99%